Psychogenic blepharospasm associated with Meige’s syndrome: a case report - Cagdas Oyku Memis; Mustafa Kurt; Gulgez Kerimova; Bilge Dogan; Doga Sevincok; Levent Sevincok (Psychiatry and Clinical Psychopharmacology, 2018)
Here we report a patient who presented a co-occurrence of Meige’s syndrome and psychogenic blepharospasm. At the first assessments, neurologists excluded conversion disorder because of the presence of a conflict and stress, absence of any markers for Meige’s syndrome, and a non-response to Botulinum toxin treatment. We determined bilateral blepharospasm, and oromandibular dystonia by neurological examination and EMG. The patient was diagnosed as primary Meige’s syndrome by the neurologists. Blepharospasm, which is triggered by emotional stress, caused secondary gains against her family. We decided that the patient had both psychogenic blepharospasm and Meige’s syndrome, which co-occurred nearly at the same interval three years ago. Similar to the seizure–pseudoseizure association, we supposed that Meige’s syndrome and concomitant psychogenic blepharospasm may indicate a coexistence of medical and conversion symptoms as in epileptic patients.